The Influence Of Creativity And Grit On Performance In Highschool Teacher Xyz In Bandar Lampung - Eka Ferawati; Debora Eflina Purba (Eduvest - Journal of Universal Studies, 2024)
The performance of high school teachers in Bandar Lampung is still low so it is necessary to look at other things that influence performance. Based on research results, the factors that influence performance are: creativity and grit. This study aims to examine the influence of creativity and grit factors on the performance of high school teachers in Bandar Lampung (N = 215). Individual Work Performance measurement is carried out using the Indonesian version of the Individual Work Performance Questionnaire (IWPQ) measuring instrument. Creativity was measured using the Indonesian version of the Runco Ideational Behavior Scale (RIBS). Grit was measured using the Short Grit Scale. The research results show that creativity has a positive and significant effect on teacher performance. The research results also show that grit has a positive and significant effect on teacher performance. The implications of this research for similar research are expected to be able to provide interventions on the variables of creativity and grit to further improve teacher performance and for teachers to continue to develop creativity and grit in order to improve their performance in the educational process.